Alkaline electrolyzed water hydrogen evolution electrode, preparation method thereof and electrolytic bath based on alkaline electrolyzed water hydrogen evolution electrode

By electrochemically depositing the catalytic layer on the surface of Rainy nickel hydrogen-making electrode with alkaline electrolytic water, and adding sulfosalicylic acid to the electroplating solution, the problem of insufficient puncture and catalytic performance of the separator is solved, and more efficient The process of electrolyzing.

CN119392280APending Publication Date: 2025-02-07JIANGSU LOPAL TECH CO LTD
View PDF 0 Cites 8 Cited by

Patent Information

Application Number
CN202411144874.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-20
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing alkaline electrolytic hydrogen-making electrodes have the risk of the separator being pierced during use, and the catalytic performance is difficult to improve, which limits the efficiency of the electrolytic process.

Method used

Using nickel mesh substrate as the basis, the surface of Rainey nickel is covered with platinum catalytic layer, nickel sulfur alloy catalytic layer, nickel cobalt zinc layer or nickel iron zinc layer through electrochemical deposition technology to form a smooth catalytic layer and in the electroplating solution Sulfosalicylic acid is added to increase the binding force of the catalytic layer to the substrate.

Benefits of technology

The risk of the diaphragm being pierced is effectively avoided, and the catalytic performance of the electrode is improved, so that its overpotential is lower than 241mV at 100mA/cm2, which improves the efficiency of the electrolytic water process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392280A_ABST
    Figure CN119392280A_ABST
Patent Text Reader

Abstract

The invention discloses an alkaline electrolytic water hydrogen evolution electrode, a preparation method thereof and an electrolytic bath based on the electrode. The electrode comprises a nickel net base material, raney nickel located on the nickel net base material and a catalytic layer which is electrochemically deposited on the surface of the raney nickel to cover a zigzag edge to form a smooth surface. The catalytic layer is a platinum catalytic layer, a nickel-sulfur alloy catalytic layer, a nickel-cobalt-zinc layer or a nickel-iron-zinc layer, and an electroplate liquid for electrochemical deposition comprises sulfosalicylic acid. According to the electrolytic cell, an alkaline electrolytic water hydrogen evolution electrode is used as a cathode, and Raney nickel / nickel net is used as an anode. According to the alkaline electrolytic water hydrogen evolution electrode, the catalyst layer which is high in binding force with the base material is deposited on the Raney nickel / nickel net base material in a specific electrochemical deposition mode, and the catalyst layer can effectively cover the sawtooth-shaped edge of the surface of the electrode and keep a part of the original high-specific-surface-surface structure of Raney nickel at the same time; the catalytic performance of the electrode is improved, and the overpotential of the electrode under 100mA / cm < 2 > can be lower than 241mV.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of alkaline water electrolysis hydrogen evolution electrode, and in particular relates to an alkaline water electrolysis hydrogen evolution electrode, a preparation method thereof and an electrolytic cell based on the electrode. Background Art

[0002] The existing water electrolysis hydrogen production routes are mainly: alkaline water electrolysis hydrogen production (ALK), proton exchange membrane water electrolysis hydrogen production (PEM), anion exchange membrane water electrolysis hydrogen production (AEM) and solid oxide electrolyte high temperature steam electrolysis hydrogen production (SOEC). Among them, AEM hydrogen production cannot be applied on a large scale due to its current immature technology. SOEC hydrogen production needs to work stably under high temperature conditions, so it is only promoted in a small range (such as nuclear power generation-SOEC combination). Although PEM hydrogen production has the advantages of fast response, no pollution, long life, and low energy consumption, it requires the use of high-cost raw materials such as precious metals, membrane electrodes, and diffusion layers, which severely limits its commercial application. ALK hydrogen production benefits from its mature technology and the use of low-cost nickel-based materials as electrodes and catalysts. It can use less or even no precious metals as catalysts, and has become the current large-scale water electrolysis hydrogen production technology route. How to reduce the energy consumption required for electrolysis during its use has become a key issue that needs to be considered.

[0003] During the operation of the alkaline electrolytic cell, the electrode is the place where the electrochemical reaction occurs. At present, people have completed the research of a variety of catalytic materials, such as precious metals: platinum, palladium, rhodium, iridium, ruthenium, etc.; non-precious metals: iron, cobalt, nickel, tin, molybdenum and their alloys, etc.; non-metals: sulfur, phosphorus and their alloys with metals such as nickel. On the one hand, by designing the components and structures of these catalytic materials on the electrode surface, the electrochemical performance of the electrode can be improved, thereby reducing power consumption; on the other hand, increasing the contact area between the active material on the electrode surface that plays a catalytic role and the solution, such as using nickel foam as a substrate, or thermally spraying nickel and aluminum powder on a nickel mesh to form a nickel-aluminum alloy, and then dissolving aluminum to form Raney nickel with a high specific surface structure, can also improve the catalytic performance of the electrode, thereby reducing the power consumption required for electrolysis.

[0004] However, in the actual commercial application of hydrogen production by alkaline water electrolysis, electrodes such as multi-element alloys, precious metals, precious metal oxides, etc. prepared by methods such as electrodeposition, chemical vapor deposition, and thermal decomposition are difficult to promote on a large scale due to factors such as cost and consistency, and the electrodes prepared by these methods are difficult to further improve their catalytic performance by increasing their surface area; although nickel foam can increase the specific surface area of ​​the catalytic material as a substrate, it will dissolve and be damaged during frequent shutdowns, resulting in a decrease in electrode performance, and cannot meet the needs of long-term operation and frequent shutdowns of alkaline electrolyzers. Therefore, even after decades of technological accumulation, mainstream commercial alkaline electrolyzers still use nickel mesh prepared by thermal spraying to obtain Raney nickel as their working electrode. However, the electrode prepared by thermal spraying technology still has the problem of diaphragm puncture. This is because when preparing Raney nickel with high specific surface area by thermal spraying technology, after dissolving aluminum in alkaline solution, the residual nickel has a jagged irregular surface. In order to improve the performance of the electrolytic cell, a zero-gap structure is used to shorten the distance between the cathode and anode, which creates the risk of diaphragm puncture and hydrogen and oxygen mixing. Moreover, the types of electrodes obtained by thermal spraying are limited. Common thermal spraying materials usually only have metal nickel, aluminum, molybdenum, iron, manganese, tungsten, and non-metals with high melting and boiling points such as carbon. Because thermal spraying has requirements on the melting and boiling points of raw materials, low-boiling point metals and non-metals such as zinc, sulfur, and phosphorus are rarely used. At the same time, during spraying, a large part of the material will pass through the nickel mesh during the spraying process and cannot be combined with it, resulting in a waste of raw materials, so precious metals are almost never used. Moreover, it is difficult to further optimize the morphology, valence state, and pore structure of the prepared catalytic material for electrodes prepared only by thermal spraying, which limits its performance development to a better method.

[0005] Based on this, there is an urgent need for a new type of alkaline water electrolysis hydrogen evolution electrode that can effectively avoid the risk of diaphragm puncture in existing electrodes while improving catalytic performance. Summary of the invention

[0006] Purpose of the invention: The technical problem to be solved by the present invention is to provide an alkaline water electrolysis hydrogen evolution electrode which can not only effectively avoid the risk of puncture of the diaphragm of the existing electrode, but also improve its catalytic performance.

[0007] Technical solution: The alkaline water electrolysis hydrogen evolution electrode of the present invention comprises a nickel mesh substrate, a Raney nickel located on the nickel mesh substrate, and a catalytic layer covered on the surface of the Raney nickel by electrochemical deposition to form a smooth surface; the catalytic layer is a platinum catalytic layer, a nickel-sulfur alloy catalytic layer, a nickel-cobalt-zinc layer or a nickel-iron-zinc layer, and the electrochemically deposited electroplating solution comprises sulfosalicylic acid.

[0008] The present invention is based on a Raney nickel / nickel mesh substrate, and a layer of catalytic material with catalytic activity is covered on the surface of the substrate by electrochemical deposition. That is, a layer of active material can be electrochemically deposited on the irregular Raney nickel through a specific electrochemical deposition process to cover the jagged edge of the electrode surface, so as to reduce the safety risk of hydrogen and oxygen mixing caused by the piercing of the diaphragm, and at the same time, excessive local deposition on the electrode surface can be avoided, so as to ensure that the electrode surface is evenly covered with the active material, and retain a part of the original high specific surface structure of the Raney nickel, so as to improve the full contact between the catalytic material on the electrode surface and the electrolyte during the electrolysis of water. In addition, by adding sulfosalicylic acid to the electroplating solution, the Raney nickel / nickel mesh substrate and the metal catalyst layer can be connected based on the action of the sulfosalicylic acid during the electrochemical deposition process, and the uniformity of the plating layer can be achieved, thereby improving the bonding strength between the deposited catalyst layer and the Raney nickel / nickel mesh substrate, and achieving the improvement of the bonding strength between the catalytic layer and the substrate of the electrode without the need for excessive deposition to effectively cover only the jagged edges of the electrode surface, without affecting the porous specific surface area characteristics of the substrate itself, and ultimately improving the catalytic performance of the electrode.

[0009] Preferably, the catalytic layer of the alkaline water electrolysis hydrogen evolution electrode of the present invention may be a nickel-cobalt-zinc layer or a nickel-iron-zinc layer. Based on the nickel-cobalt-zinc layer or the nickel-iron-zinc layer, it is possible to fully alloy it by heating after electroplating, and dissolve the amphoteric metal zinc, leaving the nickel-iron and nickel-cobalt alloys with porous structures. On the one hand, due to their high specific surface area, on the other hand, due to the catalytic activity of the nickel-iron and nickel-cobalt alloys themselves, the electrochemical performance of the electrode can be further improved. And the interface between NiFeZn and NiAl intermetallic compounds, and between NiCoZn and NiAl metal compounds can form a heterogeneous structure, further improving the catalytic performance.

[0010] Furthermore, when the catalyst for electrochemical deposition of the alkaline water electrolysis hydrogen evolution electrode of the present invention is a platinum catalyst layer, the electroplating solution used includes 96.96-98.8% water, 0.5-2% chloroplatinic acid, 0.5-2% potassium chloride and 0.2-1% sulfosalicylic acid by mass fraction.

[0011] Furthermore, when the catalyst for electrochemical deposition of the alkaline water electrolysis hydrogen evolution electrode of the present invention is a nickel-sulfur alloy catalyst layer, the electroplating solution used includes 57-70% water, 15-20% nickel sulfate, 3-5% nickel chloride, 8-12% thiourea, 3-5% boric acid and 0.2-1% sulfosalicylic acid by mass fraction.

[0012] Furthermore, when the catalyst for electrochemical deposition of the alkaline water electrolysis hydrogen evolution electrode of the present invention is a nickel-cobalt-zinc catalyst layer, the electroplating solution used includes 52-65% water, 25-35% nickel sulfate, 4-5% cobalt chloride, 2-3% zinc chloride, 3-5% boric acid and 0.2-1% sulfosalicylic acid by mass fraction.

[0013] Furthermore, when the catalyst for electrochemical deposition of the alkaline water electrolysis hydrogen evolution electrode of the present invention is a nickel-iron-zinc catalyst layer, the electroplating solution used includes 52-65% water, 25-35% nickel sulfate, 4-5% ferrous chloride, 2-3% zinc chloride, 3-5% boric acid and 0.2-1% sulfosalicylic acid by mass fraction.

[0014] The method for preparing the alkaline water electrolysis hydrogen evolution electrode of the present invention comprises the following steps:

[0015] (1) Preparing Raney nickel / nickel mesh: After pre-treating the nickel mesh, thermally spraying nickel aluminum powder on it, and then soaking it in an alkaline solution to obtain the Raney nickel / nickel mesh;

[0016] (2) Electrochemical deposition of catalyst layer: Place the Raney nickel / nickel mesh in an electrolyte at 40-60°C and a current density of 20-50 mA / cm 2 Under the above conditions, electrochemical deposition was performed for 10-30 min, followed by rinsing and drying to obtain an alkaline water electrolysis hydrogen evolution electrode.

[0017] Furthermore, in step (1) of the method for preparing an alkaline water electrolysis hydrogen evolution electrode of the present invention, the mass proportion of aluminum powder in the nickel aluminum powder is 20-50%.

[0018] Furthermore, in step (2) of the method for preparing an alkaline water electrolysis hydrogen evolution electrode of the present invention, the current density is 20-50 mA / cm 2 , the electrochemical deposition time is 10-30min.

[0019] The electrolytic cell of the present invention uses the alkaline water electrolysis hydrogen evolution electrode as a cathode and uses Raney nickel / nickel mesh as an anode.

[0020] Beneficial effect: Compared with the prior art, the significant advantages of the present invention are: the alkaline water electrolysis hydrogen evolution electrode adopts a specific electrochemical deposition method to deposit a catalyst layer with strong bonding with the substrate on the substrate of Raney nickel / nickel mesh, and the catalyst layer can effectively cover the jagged edge of the electrode surface while retaining a part of the original high specific surface structure of Raney nickel, thereby improving the catalytic performance of the overall electrode, making it 100mA / cm 2 The lower overpotential can be lower than 241mV. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The lsv curves of the platinum-plated electrodes in 1M KOH in Example 1, Example 2 and Comparative Example 1 were measured by a three-electrode system, and the potentials thereof were converted into reversible hydrogen electrode (RHE) potentials;

[0022] Figure 2The present invention measures the LSV curves of the electrodeposited nickel-sulfur alloy electrode in Example 3, Comparative Example 2, and Comparative Example 3, and the Raney nickel electrode in 1M KOH by a three-electrode system, and the potential thereof has been converted into the reversible hydrogen electrode (RHE) potential;

[0023] Figure 3 This is a surface characterization diagram of the nickel mesh of Example 1 of the present invention;

[0024] Figure 4 The surface SEM characterization of the nickel mesh of Example 1 after thermal spraying of molten nickel and aluminum powders of the present invention;

[0025] Figure 5 This is a surface characterization diagram of the Raney nickel / nickel mesh of Example 1 of the present invention;

[0026] Figure 6 This is a SEM image of the surface of the Raney nickel / nickel mesh after platinum is electrodeposited in Example 1 of the present invention (platinum / Raney nickel / nickel mesh);

[0027] Figure 7 This is a SEM image of the surface of the Raney nickel / nickel mesh after the nickel-sulfur alloy is electrodeposited in Example 3 of the present invention (nickel-sulfur / Raney nickel / nickel mesh);

[0028] Figure 8 The SEM image of the surface of the Raney nickel / nickel mesh of Example 4 of the present invention after porous nickel-cobalt-zinc is prepared (nickel-cobalt-zinc / Raney nickel / nickel mesh);

[0029] Fig. 9 The SEM image (nickel iron zinc / Raney nickel / nickel mesh) after porous nickel iron zinc is prepared on the surface of the Raney nickel / nickel mesh of Example 5 of the present invention;

[0030] Fig.10 This is a SEM image of the porous nickel-cobalt-zinc prepared on the surface of the nickel mesh in comparative example 4 of the present invention (nickel-cobalt-zinc / nickel mesh). DETAILED DESCRIPTION

[0031] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0032] It should be noted that the raw materials used in the present invention can all be purchased from commercial sources.

[0033] Example 1

[0034] The alkaline water electrolysis hydrogen evolution electrode of Example 1 comprises a nickel mesh substrate, a Raney nickel on the nickel mesh substrate, and a platinum catalyst layer coated on the surface of the Raney nickel by electrochemical deposition to form a smooth surface. The electroplating solution used for the electrochemical deposition is 98.49% water, 0.01% chloroplatinic acid (the platinum content in the chloroplatinic acid is 38%), 1.2% potassium chloride, and 0.3% sulfosalicylic acid.

[0035] The electrode preparation method of this embodiment 1 comprises the following steps:

[0036] (1) Preparation of Raney nickel / nickel mesh: A nickel mesh with a wire diameter of 0.3 mm and a length and width of 10 mm was used. It was sandblasted and soaked in 20% hydrochloric acid for 30 min, and then ultrasonically cleaned in acetone, anhydrous ethanol and ultrapure water for 20 min each. Nickel aluminum powder containing 40% aluminum by mass was thermally sprayed on it. The sprayed electrode was placed in 100 mL of 20% sodium hydroxide solution at 60°C and soaked for 16 h until the aluminum was completely dissolved, thereby obtaining a Raney nickel / nickel mesh.

[0037] (2) Electrochemical deposition of catalyst layer: Raney nickel / nickel mesh was placed in an electrolyte at 40°C and a current density of 50 mA / cm 2 Under the above conditions, electrochemical deposition was carried out for 10 min, followed by rinsing and drying to obtain an alkaline water electrolysis hydrogen evolution electrode.

[0038] Overpotential performance test: At room temperature 25℃, in 1M KOH solution, 3×3cm 2 The three-electrode system was composed of a platinum sheet as the counter electrode, a mercuric oxide electrode as the reference electrode, and a platinum / Raney nickel / nickel mesh as the working electrode. The current was 200 mA / cm 2 The current density was first activated for 600s, and the line sweep voltammetry (LSV) curve was tested at a scan rate of 10mV / s. The results are shown in Figure 1 As shown, its 100mA / cm 2 The lower overpotential is 173mV.

[0039] Structural characterization: The surfaces of the nickel mesh pretreated in Example 1, the nickel mesh after thermal spraying of molten nickel / aluminum powder, and the Raney nickel / nickel mesh were characterized, and the results obtained are as follows: Figures 3 to 5 As shown. Figures 3 to 5 It can be seen that a layer of nickel-aluminum alloy can be obtained on the relatively smooth surface of the nickel mesh through thermal spraying. After the nickel mesh covered with nickel-aluminum alloy is immersed in a strong alkaline solution to remove the aluminum, the remaining nickel has a larger specific surface area; at the same time, due to the dissolution of aluminum, the remaining nickel forms a part of serrated morphology on the surface.

[0040] In addition, the surface structure of the platinum / Raney nickel / nickel mesh prepared in Example 1 was characterized, and the results obtained are as follows: Figure 6 As shown. Figure 6 It can be seen that the platinum deposited on the surface of Raney nickel / nickel mesh covers the jagged edges of Raney nickel formed by aluminum dissolution, while retaining the original high specific surface area porous structure of Raney nickel.

[0041] Example 2

[0042] The basic steps are the same as those in Example 1, except that the content of chloroplatinic acid in the plating solution, i.e., more chloroplatinic acid is added, specifically comprising 98.46% water, 0.04% chloroplatinic acid (the platinum content in the chloroplatinic acid is 38%), 1.2% potassium chloride and 0.3% sulfosalicylic acid.

[0043] Overpotential performance test: At room temperature 25℃, in 1M KOH solution, 3×3cm 2 The three-electrode system was composed of a platinum sheet as the counter electrode, a mercuric oxide electrode as the reference electrode, and a platinum / Raney nickel / nickel mesh as the working electrode. The current was 200 mA / cm 2 The current density was first activated for 600s, and the line sweep voltammetry (LSV) curve was tested at a scan rate of 10mV / s. The results are shown in Figure 1 As shown, its 100mA / cm 2 The lower overpotential is 184mV.

[0044] Comparative Example 1

[0045] The basic steps are the same as those in Example 1, except that electrochemical deposition is performed on the pretreated nickel mesh, and the electroplating solution used is different, with more chloroplatinic acid added, specifically comprising 98.46% water, 0.04% chloroplatinic acid (the platinum content in the chloroplatinic acid is 38%), 1.2% potassium chloride, and 0.3% sulfosalicylic acid.

[0046] Overpotential performance test: At room temperature 25℃, in 1M KOH solution, 3×3cm 2 The three-electrode system was composed of a platinum sheet as the counter electrode, a mercuric oxide electrode as the reference electrode, and a platinum / Raney nickel / nickel mesh as the working electrode. The current was 200 mA / cm 2 The current density was first activated for 600s, and the line sweep voltammetry (LSV) curve was tested at a scan rate of 10mV / s. The results are shown in Figure 1 As shown, its 100mA / cm 2 The lower overpotential is 196 mV.

[0047] Combining Example 1 and Comparative Example 1, it can be seen that the overpotential of the electrode prepared by increasing the loading of the catalyst layer based only on the nickel mesh is increased. It can be seen that the electrode of the present invention not only has a lower overpotential and excellent catalytic performance by using an electrode with a less loaded platinum catalyst layer / Raney nickel / nickel mesh, but also can cover the jagged edge of the electrode surface and retain a part of the original high specific surface structure of Raney nickel, so as to improve the full contact between the electrode surface catalytic material and the electrolyte during the electrolysis of water, and has high catalytic performance.

[0048] Example 3

[0049] The alkaline water electrolysis hydrogen evolution electrode of Example 3 comprises a nickel mesh substrate, a Raney nickel on the nickel mesh substrate, and a nickel-sulfur alloy catalyst layer coated on the surface of the Raney nickel by electrochemical deposition to form a smooth surface. The electrochemical deposition uses 62% water, 18% nickel sulfate, 4% nickel chloride, 10% thiourea, 5% boric acid, and 1% sulfosalicylic acid.

[0050] The electrode preparation method of this embodiment 3 comprises the following steps:

[0051] (1) Preparation of Raney nickel / nickel mesh: A nickel mesh with a wire diameter of 0.3 mm and a length and width of 20 mm was used. It was sandblasted and soaked in 20% hydrochloric acid for 30 min, and then ultrasonically cleaned in acetone, anhydrous ethanol and ultrapure water for 20 min each. Nickel aluminum powder containing 50% aluminum by mass was thermally sprayed on it. The sprayed electrode was placed in 100 mL of 20% sodium hydroxide solution at 60°C and soaked for 16 h until the aluminum was completely dissolved, thereby obtaining a Raney nickel / nickel mesh.

[0052] (2) Electrochemical deposition of catalyst layer: Raney nickel / nickel mesh was placed in an electrolyte at 40°C and a current density of 20 mA / cm 2 Under the above conditions, electrochemical deposition was carried out for 1400s, followed by rinsing and drying to obtain an alkaline water electrolysis hydrogen evolution electrode.

[0053] Overpotential performance test: At room temperature 25℃, in 1M KOH solution, 3×3cm 2 The three-electrode system was composed of a platinum sheet as the counter electrode, a mercuric oxide electrode as the reference electrode, and a nickel-sulfur / Raney nickel / nickel mesh as the working electrode. The current was 200 mA / cm 2 The current density was first activated for 600s, and the LSV was tested at a scan rate of 10mV / s. The results are as follows Figure 2 As shown, its 100mA / cm 2 The lower overpotential is 241mV.

[0054] Structural characterization: The surface of the nickel-sulfur / Raney nickel / nickel mesh prepared in Example 3 was structurally characterized, and the results obtained are as follows: Figure 7 As shown. Figure 7 It can be seen that the nickel-sulfur alloy deposited on the surface of the Raney nickel / nickel mesh covers its jagged edges and retains the original porous structure of the Raney nickel.

[0055] Comparative Example 2

[0056] The basic steps are the same as those in Example 3, except that sulfosalicylic acid is not added to the electroplating solution. Specifically, the electroplating solution includes 63% water, 18% nickel sulfate, 4% nickel chloride, 10% thiourea, and 5% boric acid. The LSV is measured as Figure 2 As shown, its 100mA / cm2 The overpotential under current is 248mV.

[0057] Comparative Example 3

[0058] The basic steps are the same as those in Example 3, except that a nickel mesh is used as the substrate to deposit the nickel-sulfur alloy. The LSV is measured as follows: Figure 2 As shown, its 100mA / cm 2 The overpotential under current is 269mV.

[0059] Example 4

[0060] The alkaline water electrolysis hydrogen evolution electrode of Example 4 comprises a nickel mesh substrate, a Raney nickel on the nickel mesh substrate, and a nickel-cobalt-zinc catalyst layer that is electrochemically deposited on the surface of the Raney nickel to form a smooth surface. The electrochemical deposition uses 56.5% water, 32% nickel sulfate, 4% cobalt chloride, 2.5% zinc chloride, 5% boric acid, and 1% sulfosalicylic acid.

[0061] The electrode preparation method of this embodiment 4 comprises the following steps:

[0062] (1) Preparation of Raney nickel / nickel mesh: A nickel mesh with a wire diameter of 0.3 mm and a length and width of 20 mm was used. It was sandblasted and soaked in 20% hydrochloric acid for 30 min, and then ultrasonically cleaned in acetone, anhydrous ethanol and ultrapure water for 20 min each. Nickel aluminum powder containing 20% ​​aluminum by mass was thermally sprayed on it. The sprayed electrode was placed in 150 mL of 20% sodium hydroxide solution at 60°C and soaked for 16 h until the aluminum was completely dissolved, thereby preparing a Raney nickel / nickel mesh.

[0063] (2) Electrochemical deposition of catalyst layer: Raney nickel / nickel mesh was placed in electrolyte at 60°C and current density of 50 mA / cm 2 Under the conditions, electrochemical deposition is carried out for 30 minutes; the obtained electrode is placed in a tubular furnace and treated at 600°C for 3 hours. After cooling, it is placed in a 60°C, 20% sodium hydroxide solution for 12 hours to obtain a nickel-cobalt-zinc / Raney nickel / nickel mesh electrode with a porous structure.

[0064] Overpotential performance test: At room temperature 25℃, in 1M KOH solution, 3×3cm 2 The three-electrode system was composed of a platinum sheet as the counter electrode, a mercuric oxide electrode as the reference electrode, and a nickel-cobalt-zinc / Raney nickel / nickel mesh as the working electrode. The current was 200 mA / cm 2 The current density was first activated for 600s, and the LSV was tested at a scan rate of 10mV / s. 2 The lower overpotential is 225mV.

[0065] Structural characterization: The surface structure of the nickel-cobalt-zinc / Raney nickel / nickel mesh prepared in Example 4 was characterized, and the results obtained are as follows: Figure 8 As shown. Figure 8 It can be seen that the nickel, cobalt and zinc prepared on the surface of Raney nickel / nickel mesh covers the original jagged edges of Raney nickel. The surface of nickel, cobalt and zinc after alkali washing is relatively smooth, and the gaps formed after alkali washing to remove zinc are conducive to the contact between more active materials on the electrode surface and the solution and the escape of hydrogen bubbles.

[0066] Comparative Example 4

[0067] The basic steps of Comparative Example 4 are the same as those of Example 4, except that a nickel mesh is used as a substrate to electro-deposit a nickel-cobalt-zinc alloy, and then a porous nickel-cobalt-zinc electrode is prepared by post-treatment. Fig.10 It can be seen that its surface is relatively flat as a whole. Figure 8 The area in contact with the solution is smaller, and the measured current is 100mA / cm 2 The overpotential under current is 241mV.

[0068] Example 5

[0069] The alkaline water electrolysis hydrogen evolution electrode of this embodiment 5 comprises a nickel mesh substrate, a Raney nickel on the nickel mesh substrate, and a nickel-iron-zinc catalyst layer that is electrochemically deposited on the surface of the Raney nickel to form a smooth surface. The electrochemical deposition uses 56.5% water, 32% nickel sulfate, 4% ferrous chloride, 2.5% zinc chloride, 5% boric acid, and 1% sulfosalicylic acid.

[0070] The electrode preparation method of this embodiment 5 comprises the following steps:

[0071] (1) Preparation of Raney nickel / nickel mesh: A nickel mesh with a wire diameter of 0.3 mm and a length and width of 30 mm was used. It was sandblasted and soaked in 20% hydrochloric acid for 30 min, and then ultrasonically cleaned in acetone, anhydrous ethanol and ultrapure water for 20 min each. Nickel-aluminum powder containing 30% aluminum by mass was thermally sprayed on it. The sprayed electrode was placed in 150 mL of 20% sodium hydroxide solution at 60°C and soaked for 16 h until the aluminum was completely dissolved. This was recorded as Raney nickel / nickel mesh.

[0072] (2) Electrochemical deposition of catalyst layer: Raney nickel / nickel mesh was placed in electrolyte at 60°C and current density of 50 mA / cm 2 Under the conditions, electrochemical deposition is carried out for 30 minutes; after completion, the electrode is rinsed and dried, placed in a tube furnace, treated at 600°C for 6 hours, and after cooling, placed in a 60°C, 20% sodium hydroxide solution for 16 hours to obtain a nickel-iron-zinc / Raney nickel / nickel mesh electrode with a porous structure.

[0073] Overpotential performance test: At room temperature 25℃, in 1M KOH solution, with a 4×4cm 2 The three-electrode system was composed of a platinum sheet as the counter electrode, a mercuric oxide electrode as the reference electrode, and a nickel-iron-zinc / Raney nickel / nickel mesh as the working electrode. The current was 200 mA / cm 2 The current density was first activated for 600s, and the LSV was tested at a scan rate of 10mV / s. 2 The lower overpotential is 232mV.

[0074] Structural characterization: The surface of the nickel-iron-zinc / Raney nickel / nickel mesh prepared in Example 5 was structurally characterized, and the results obtained are as follows: Fig. 9 As shown. Fig. 9 It can be seen that the nickel-iron-zinc prepared on the surface of Raney nickel / nickel mesh covers the original jagged edge of Raney nickel. The surface of nickel-cobalt-zinc after alkali washing is relatively smooth, and the holes formed after alkali washing to remove zinc are conducive to the contact between more active materials on the electrode surface and the solution.

[0075] It can be seen from the above embodiments and comparative examples that the catalytic performance of the platinum / Raney nickel / nickel mesh electrode prepared using platinum as the catalyst layer is better than that of the nickel sulfur / Raney nickel / nickel mesh electrode, the nickel cobalt zinc / Raney nickel / nickel mesh electrode and the nickel cobalt zinc / Raney nickel / nickel mesh electrode, but at the same time its cost is relatively high. Compared with the nickel sulfur / Raney nickel / nickel mesh electrode, the catalytic performance of the nickel cobalt zinc / Raney nickel / nickel mesh electrode and the nickel cobalt zinc / Raney nickel / nickel mesh electrode is better.

[0076] In addition, the bonding force between the catalyst layer and the substrate of Example 1, Example 3 to Example 5, and Comparative Example 2 of the present invention was detected, that is, the platinum / Raney nickel / nickel mesh electrode, nickel sulfur / Raney nickel / nickel mesh electrode, nickel cobalt zinc / Raney nickel / nickel mesh electrode and nickel cobalt zinc / Raney nickel / nickel mesh electrode prepared in Example 1, Example 3 to 5, and the nickel sulfur / Raney nickel / nickel mesh electrode prepared in Comparative Example 2 were vibrated under ultrasonic conditions for 30 minutes, and then taken out, rinsed, and dried for mass measurement. The results obtained are shown in Table 1 below.

[0077] Table 1 Catalytic layer bonding performance test of Example 1, Examples 3 to 5 and Comparative Example 2

[0078]

[0079] It can be seen from Table 1 that when the electrode is prepared in the present invention, by adding sulfosalicylic acid to the electroplating solution, the bonding force between the electrochemically deposited catalytic layer and the Raney nickel / nickel mesh substrate can be effectively improved, so that the catalytic layer peeling is less than or equal to 0.2 mg.

[0080] In addition to the above embodiments, when electrochemically depositing a platinum catalyst layer, the electroplating solution used in the present invention may also include 96.96-98.8% water, 0.01-0.04% chloroplatinic acid, 0.5-2% potassium chloride and 0.2-1% sulfosalicylic acid by mass fraction. When electrochemically depositing a nickel-sulfur alloy catalyst layer, the electroplating solution used may also include 57-70% water, 15-20% nickel sulfate, 3-5% nickel chloride, 8-12% thiourea, 3-5% boric acid and 0.2-1% sulfosalicylic acid by mass fraction. When electrochemically depositing a nickel-cobalt-zinc catalyst layer, the electroplating solution used may also include 52-65% water, 25-35% nickel sulfate, 4-5% cobalt chloride, 2-3% zinc chloride, 3-5% boric acid and 0.2-1% sulfosalicylic acid by mass fraction. When electrochemically depositing the nickel-iron-zinc catalyst layer, the electroplating solution used may also include 52-65% water, 25-35% nickel sulfate, 4-5% ferrous chloride, 2-3% zinc chloride, 3-5% boric acid and 0.2-1% sulfosalicylic acid by mass fraction. The current density used in the electrochemical deposition of the present invention may be 10-70 mA / cm 2 The electrochemical deposition time can be 10-40 min; preferably, the current density can be 20-50 mA / cm 2 , electrochemical deposition time is 10-30min.

Claims

1. An alkaline water electrolysis hydrogen evolution electrode, characterized in that The electrode comprises a nickel mesh substrate, a Raney nickel on the nickel mesh substrate, and a catalytic layer electrochemically deposited on the surface of the Raney nickel to cover the jagged edges to form a smooth surface; the catalytic layer is a platinum catalytic layer, a nickel-sulfur alloy catalytic layer, a nickel-cobalt-zinc layer or a nickel-iron-zinc layer, and the electrochemically deposited electroplating solution comprises sulfosalicylic acid.

2. The alkaline water electrolysis hydrogen evolution electrode according to claim 1, characterized in that The catalytic layer is a nickel-cobalt-zinc layer or a nickel-iron-zinc layer.

3. The alkaline water electrolysis hydrogen evolution electrode according to claim 1, characterized in that When the catalyst for electrochemical deposition is a platinum catalyst layer, the electroplating solution used includes 96.96-98.8% water, 0.01-0.04% chloroplatinic acid, 0.5-2% potassium chloride and 0.2-1% sulfosalicylic acid by mass fraction.

4. The alkaline water electrolysis hydrogen evolution electrode according to claim 1, characterized in that When the electrochemically deposited catalyst is a nickel-sulfur alloy catalyst layer, the electroplating solution used includes 57-70% water, 15-20% nickel sulfate, 3-5% nickel chloride, 8-12% thiourea, 3-5% boric acid and 0.2-1% sulfosalicylic acid by mass fraction.

5. The alkaline water electrolysis hydrogen evolution electrode according to claim 1 or 3, characterized in that: When the electrochemically deposited catalyst is a nickel-cobalt-zinc catalyst layer, the electroplating solution used includes 52-65% water, 25-35% nickel sulfate, 4-5% cobalt chloride, 2-3% zinc chloride, 3-5% boric acid and 0.2-1% sulfosalicylic acid by mass fraction.

6. The alkaline water electrolysis hydrogen evolution electrode according to claim 1 or 3, characterized in that: When the electrochemically deposited catalyst is a nickel-iron-zinc catalyst layer, the electroplating solution used includes 52-65% water, 25-35% nickel sulfate, 4-5% ferrous chloride, 2-3% zinc chloride, 3-5% boric acid and 0.2-1% sulfosalicylic acid by mass fraction.

7. A method for preparing the alkaline water electrolysis hydrogen evolution electrode according to claim 1, characterized in that: The steps include: (1) Preparing Raney nickel / nickel mesh: After pre-treating the nickel mesh, thermally spraying nickel aluminum powder on it, and then soaking it in an alkaline solution to obtain the Raney nickel / nickel mesh; (2) Electrochemical deposition of catalyst layer: Place the Raney nickel / nickel mesh in an electrolyte at 40-60°C and a current density of 10-70 mA / cm 2 Under the above conditions, electrochemical deposition was performed for 10-40 min, followed by rinsing and drying to obtain an alkaline water electrolysis hydrogen evolution electrode.

8. The method for preparing an alkaline water electrolysis hydrogen evolution electrode according to claim 7, characterized in that: In step (1), the mass proportion of aluminum powder in the nickel aluminum powder is 20-50%.

9. The method for preparing an alkaline water electrolysis hydrogen evolution electrode according to claim 7, characterized in that: In step (2), the current density is 20-50 mA / cm 2 , the electrochemical deposition time is 10-30min.

10. An electrolytic cell, characterized in that: The electrolytic cell uses the alkaline water electrolysis hydrogen evolution electrode as claimed in claim 1 as a cathode and uses Raney nickel / nickel mesh as an anode.

Citation Information

Cited By

  • Method for optimizing hydrogen evolution performance of Raney nickel electrode in alkaline electrolytic cell

    CN119553310A

  • A method for optimizing hydrogen evolution performance of Raney nickel electrode in alkaline electrolyzer

    CN119553310B

  • Boron-doped Raney nickel electrode, preparation method and application

    CN121250497A

  • Boron-doped raney nickel electrode, method of preparation and use

    CN121250497B

  • Double-layer Raney nickel electrode, preparation method and application

    CN121344643A